Freelance platform work in the Russian Federation: 2009-2019 - Andrey Shevchuk; Denis Strebkov (International Labour Organization (ILO), 2021)
This paper traces the development of freelance platform work in the Russian Federation based on unique data from four online surveys conducted over the period 2009 and 2019 via the leading platform for creative and knowledge-based work and analyses the working conditions and well-being of the workers @At the dawn of the twenty-first century, freelance work through online platforms emerged as a new phenomenon, gradually becoming a distinctive feature of the digital economy. This paper traces the development of freelance platform work in the Russian Federation and the wider post-Soviet space. The study utilizes unique data from four online surveys conducted by the authors in 2009, 2011, 2014 and 2019 via the leading general-purpose platform for creative and knowledge-based work, FL.ru operating in the Russian language. The common methodology used to collect and analyse the data from each survey provides an opportunity to shed light on the dynamics of key indicators over the ten-year period. The study investigates socio-demographic characteristics of freelancers and their careers, motivations, working conditions and well-being, as well as the problems that freelancers encounter in their relationships with clients. Overall, the results point to the increased importance of platforms, the diffusion of the new model of work among the wider population, and the persistent informality that may hinder the future development of the online labour market. The lack of basic labour rights, collective representation and social protection is also a pressing concern.
Keywords: 330; non-standard employment; self-employment; freelancers; gig economy; platform work; online labour markets; Russian Federation